Once again on mathematics teachers training - Stankus, Eugenijus (Lietuvos matematikos rinkinys, 2013)
In this paper the sensitive problems of school mathematics teaching and mathematics teachers training are analysed. Are degree programs, preparing mathematics and informatics teachers, provides enough knowledge that graduates are able to be good teachers? These and other issues, related to realities, an attempt to answer in the article.